Characterisation of immunoparesis in newly diagnosed myeloma and its impact on progression-free and overall survival in both old and recent myeloma trials - Jennifer Heaney; John P. Campbell; Gulnaz Iqbal; David A. Cairns; Alex Richter; J. A. Child; Walter M. Gregory; Graham Jackson; Martin Kaiser; Roger G. Owen; Faith E. Davies; Gareth J. Morgan; et al. (2018)
We measured immunosuppression at myeloma diagnosis and assessed the impact on survival in 5826 UK myeloma trial patients. Polyclonal immunoglobulin levels were below normal in 85% of patients and above normal in only 0.4% of cases for IgA, 0.2% for IgM and no cases for IgG. Immunoparesis had a greater impact in recent trials: median overall survival (OS) was up to 3 years longer for patients without immunoparesis compared to the old trials, less than 1 year longer. Median progression-free survival (PFS) was 39%, 36% and 57% longer for patients with normal IgG, IgA and IgM levels, respectively. The depth of IgM suppression, but not the depth of IgG or IgA suppression, was prognostic for survival: the most severely suppressed IgM tertile of patients OS was 0.9 years shorter than those in the top tertile, and 2.6 years shorter than OS of those with normal IgM levels (p = .007). The degree of suppression of polyclonal IgM levels below normal was associated with worse PFS (p = .0002). Infection does not appear to be the main mechanism through which immunoparesis affects survival. We hypothesise that IgM immunoparesis impacts through a combination of being associated with more aggressive disease and reduced immune surveillance against relapse.